BORDER TRADE EFFECT ON INDONESIA’S EXPORT: GRAVITY MODEL ANALYSIS - Septania Rubi Prameswari; Mochammad As'adur Rofiq (Intermestic: Journal of International Studies, 2025)
Grounded in Adam Smith’s theory of trade favoring high-GDP and proximate partners, we analyze determinants including GDP, Free Trade Agreements (FTAs), Logistics Performance Index (LPI), language, shared borders, and distance across Indonesia’s top 30 export partners (2019–2023). Unlike prior studies, we integrate LPI and border effects into a gravity model, addressing endogeneity with Poisson Pseudo Maximum Likelihood (PPML) estimation alongside OLS, FEM, and REM. Results indicate that LPI is the most significant driver, while distance has a negative impact on trade, confirming the advantage of proximity. Contrary to expectations, FTAs showed limited significance, suggesting non-tariff barriers may dominate. Policy implications highlight the importance of investments in port modernization and customs digitization to capitalize on trade with high-GDP neighbors, alongside strategic agreements with distant, high-growth markets.